2023
DOI: 10.1186/s13287-023-03502-5
|View full text |Cite
|
Sign up to set email alerts
|

Personalized medicine in the dish to prevent calcium leak associated with short-coupled polymorphic ventricular tachycardia in patient-derived cardiomyocytes

Yvonne Sleiman,
Steven Reiken,
Azzouz Charrabi
et al.

Abstract: Background Polymorphic ventricular tachycardia (PMVT) is a rare genetic disease associated with structurally normal hearts which in 8% of cases can lead to sudden cardiac death, typically exercise-induced. We previously showed a link between the RyR2-H29D mutation and a clinical phenotype of short-coupled PMVT at rest using patient-specific hiPSC-derived cardiomyocytes (hiPSC-CMs). In the present study, we evaluated the effects of clinical and experimental anti-arrhythmic drugs on the intracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The impairment of SR function has proven to be predominantly induced by a SR Ca 2+ load reduction due to decreased activity of the SERCA and also from the RYR2 leak ( 102 104 ). It is associated with a Ca 2+ leak from the SR through the RYR2 and a higher RYR2 activity ( 105 , 106 ). Other studies have highlighted that the SR Ca 2+ leak triggers mitochondrial dysfunction and leads to an increased production of free radicals, which in turn leads to pathological RYR2 remodeling ( 107 ).…”
Section: Electrical Remodelingmentioning
confidence: 99%
“…The impairment of SR function has proven to be predominantly induced by a SR Ca 2+ load reduction due to decreased activity of the SERCA and also from the RYR2 leak ( 102 104 ). It is associated with a Ca 2+ leak from the SR through the RYR2 and a higher RYR2 activity ( 105 , 106 ). Other studies have highlighted that the SR Ca 2+ leak triggers mitochondrial dysfunction and leads to an increased production of free radicals, which in turn leads to pathological RYR2 remodeling ( 107 ).…”
Section: Electrical Remodelingmentioning
confidence: 99%
“…The study demonstrated that the BTHS cardiomyopathy phenotype is easily reversed by reintroducing wild-type (WT) TAZ or inhibiting excess reactive oxygen species (ROS) by BTHS mitochondria. In addition, Sleiman et al modified patient-derived induced CM in patients with pleomorphic ventricular tachycardia caused by RyR2-H29D mutation through gene editing, resulting in a shortened action potential and the restoration of typical arrhythmias and contractions [ 169 , 170 ].…”
Section: Application Of Cardiovascular Organoidsmentioning
confidence: 99%